Fiber density and cross‐section correlates with tau burden in entorhinal cortex in healthy older adults: Neuroimaging / multi‐modal comparisons. (7th December 2020) - Gazes, Yunglin; Mensing, Ashley; Luo, Linggang; Razlighi, Qolamreza; Kreisl, William Charles
Abstract: Background: Tau PET imaging, while highly predictive of the onset of dementia, requires injection of radioactive compound and costs much more than MRI scans. The goal of this study was to test whether multi‐shell diffusion MRI can generate diffusion measures that predict tau burden. While DTI measures such as fractional anisotropy (FA) and mean diffusivity have been examined in aging and dementia studies, the DTI model is now recognized as being too simplistic and has been shown to mistakenly calculated higher FA than controls in atrophied white matter. Multi‐shell diffusion MRI allows more accurate modeling of crossing fibers and has been demonstrated to detect atrophy in Alzheimer's disease. Method: In the current study, a sample of 14 healthy older adults was scanned with multi‐shell diffusion MRI and tau PET imaging using [18 F ]MK‐6240 tracer. For 10 of the participants, diffusion was obtained on average 222 days before tau PET while the 4 other participants were scanned with diffusion MRI 211 days after tau PET. Standardized uptake value ratio (SUVR) for the left and the right entorhinal cortex were quantified relative to the cerebellar mean uptake. Diffusion data were processed through MRtrix's fiber‐based analysis pipeline to obtain the whole brain fiber density and cross‐section (FDC) measure. Using tracts connected to the parahippocampal gyrus as masks, we tested whether FDC of the fibers in the white matter tracts connected to the parahippocampal gyrus correlated negatively with the tau SUVR in the entorhinal cortex within each hemisphere, correcting for age. Result: After correction for multiple comparisons using family‐wise error approach, FDC for fibers connected to the left parahippocampal gyrus were negatively correlated with the left entorhinal tau SUVR as shown in figure attached. The mean FDC over the significant fibers and EC tau SUVR showed that r = ‐.707, p=0.007. Conclusion: The negative correlation supports our hypothesis that greater tau burden is associated with lower fiber density and cross‐section in white matter tracts directly connected to the parahippocampal cortex. This encouraging result demonstrates the potential for multi‐shell diffusion as an alternative to PET for early detection of tau burden in cognitively healthy older adults.